2015
DOI: 10.3758/s13414-015-0905-6
|View full text |Cite
|
Sign up to set email alerts
|

When can attention influence binocular rivalry?

Abstract: Attentional influence over perception is particularly pronounced when sensory stimulation is ambiguous, where attention can reduce stimulus uncertainty and promote a stable interpretation of the world. However, binocular rivalry, an extensively studied visual ambiguity, has proved to be comparatively resistant to attentional modulation. We hypothesize that this apparent inconsistency reflects fluctuations in the degree of unresolved competition during binocular rivalry. Namely, attentional influence over rival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 49 publications
(91 reference statements)
4
23
3
Order By: Relevance
“…A recent study showed that stimuli under CFS elicited high-level behavioral priming effects only under conditions of partial awareness, but not when fully suppressed (Gelbard-Sagiv et al, 2016). Similarly, a recent study demonstrated that manipulations of attention only affected dominance durations in a binocular rivalry paradigm around the time of perceptual transitions (Dieter et al, 2015). Another binocular rivalry study showed that the detection performance of monocular probes followed gradual changes in consciousness, rather than being dichotomous (Alais et al, 2010).…”
Section: Discussionmentioning
confidence: 84%
“…A recent study showed that stimuli under CFS elicited high-level behavioral priming effects only under conditions of partial awareness, but not when fully suppressed (Gelbard-Sagiv et al, 2016). Similarly, a recent study demonstrated that manipulations of attention only affected dominance durations in a binocular rivalry paradigm around the time of perceptual transitions (Dieter et al, 2015). Another binocular rivalry study showed that the detection performance of monocular probes followed gradual changes in consciousness, rather than being dichotomous (Alais et al, 2010).…”
Section: Discussionmentioning
confidence: 84%
“…Observers who are instructed to "hold" one of the two rival targets dominant exhibit relatively little influence over the dynamics of binocular rivalry (3). Rivalry becomes more susceptible to selective modulation under conditions that promote the deployment of attention to features present in only one of the two rivalry targets (4)(5)(6)(7). However, compared with strong effects of visual attention on perception in other domains (8,9), these effects are modest and suggest additional limiting conditions on attention's ability to influence perception during binocular rivalry (10).…”
mentioning
confidence: 99%
“…Hence, it is possible that the increased salience might have contributed to suppression through attentional capture. However, attention alone cannot account for mask size and contrast effects, as it is more likely to influence BR dynamics at the end of dominance periods (Dieter, Melnick, & Tadin, 2015), when suppression is the weakest (Alais, Cass, O'Shea & Blake, 2010). Moreover, given that the task was to identify the orientation of the target, it seemed counterintuitive for participants to direct their attention to the mask and try to maintain its dominance.…”
Section: Discussion For Experiments 1-2mentioning
confidence: 99%